PERAN MEDIA SOSIAL DALAM MEMBANGUN CITRA DESTINASI PARIWISATA YANG MENARIK - Andzani , Diva; Virgin, Diah; Setijadi , Naniek (FEB Universitas Sam Ratulangi Manado, 2024)
Abstract. This study aims to investigate the role of social media in shaping the image of tourist destinations. Using a qualitative descriptive research method, the study highlights the shift in the paradigm of tourism marketing to social media platforms such as Instagram, Facebook, Twitter, and TikTok. The results indicate that social media enables destinations to build a personal and attractive image through strong narratives and visual content. Visualization on these platforms is crucial in shaping the allure of destinations. Storytelling is also found to play a crucial role in creating an authentic image and building emotional connections with tourists. The study identifies challenges such as reputation management and crisis mitigation in the use of social media. In conclusion, social media is not only a promotional tool but also a key element in creating the appeal of tourist destinations and building emotional relationships with users. Abstrak. Studi ini bertujuan menyelidiki peran media sosial dalam membentuk citra destinasi pariwisata. Dengan metode penelitian kualitatif deskriptif, penelitian ini menyoroti pergeseran paradigma pemasaran pariwisata ke media sosial seperti Instagram, Facebook, Twitter, dan TikTok. Hasilnya menunjukkan bahwa media sosial memungkinkan destinasi membangun citra pribadi dan menarik melalui narasi kuat dan konten visual. Visualisasi di platform ini menjadi kunci dalam membentuk daya tarik destinasi. Storytelling juga ditemukan berperan penting dalam menciptakan citra autentik, membangun hubungan emosional dengan wisatawan. Studi mengidentifikasi tantangan seperti manajemen reputasi dan penanggulangan krisis dalam pemanfaatan media sosial. Kesimpulannya, media sosial bukan hanya alat promosi, tetapi juga elemen kunci dalam menciptakan daya tarik destinasi pariwisata dan membangun hubungan emosional dengan pengguna.